Detection of Cervical Uterine Cancer: cytology after 25 years old? - Eneida Bravo Polanco; Narciso Águila Rodríguez (Medisur)
In Cuba, as in other western countries, Cervical Uterine Cancer is in the second place of oncological morbidity in women from 20 to 30 years old. There also studies which show deficient information about adolescents regarding sexually transmitted diseases and their consequences, among them developing cancer. This article is aimed at reflecting about the incidence of this disease at early ages; however the program for its detection includes performing cytology starting at 25 year old. It necessary then, to think the measures to be taken so that this scourge does not affect young women.